2018
DOI: 10.1111/nmo.13283
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial actions of microbiota‐derived tryptophan metabolites

Abstract: Tryptophan is an important dietary amino acid and it is the precursor for 5-hydroxytryptamine synthesis in the nervous system and by enterochromaffin cells in the gut mucosa. Tryptophan is also metabolized by enzymes in the gut mucosa and also by enzymes produced by the gut microbiome. Diet and the microbiome can contribute to metabolic disease in part by causing intestinal inflammation and increased permeability. In this issue of Neurogastroenterology and Motility, Jennis et al. test the hypothesis that indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Secondary metabolites from microbiota such as tryptamine, which can serve as hormones or signaling molecules ( 136 ) to “control” the host physiology and behavior, are also known for plants. Indole-3-acetic acid (IAA), one of the most important plant growth regulators, is also derived from the tryptophan metabolism of PGPM such as Pseudomonadaceae ( 137 ).…”
Section: Microbial Metabolites: Beneficial and Deleterious Effects Ofmentioning
confidence: 99%
“…Secondary metabolites from microbiota such as tryptamine, which can serve as hormones or signaling molecules ( 136 ) to “control” the host physiology and behavior, are also known for plants. Indole-3-acetic acid (IAA), one of the most important plant growth regulators, is also derived from the tryptophan metabolism of PGPM such as Pseudomonadaceae ( 137 ).…”
Section: Microbial Metabolites: Beneficial and Deleterious Effects Ofmentioning
confidence: 99%
“…Metabolite production is a critical factor by which the microbiota can regulate different systems. These metabolites circulate in the blood and then interact with local tissues ( 28 30 ). From previous results, it was already known that the microbiotas of all mice treated with antibiotics are similar in distribution and properties, regardless of whether they are treated with or without γδT cell therapy.…”
Section: Resultsmentioning
confidence: 99%
“…3E), a key component of the immune response at barrier sites by acting on epithelial renewal and barrier integrity, and thus it is quite crucial for intestinal homeostasis (30) . In the indole/AhR pathway, indoleacetate is a ligand for AhR and known to affect the intestinal permeability and host immunity (36) . The animal experiment has revealed that AhR activation generally reduces in ammation and thus maintains gut homeostasis (37) .…”
Section: Discussionmentioning
confidence: 99%